Persepsi Minat Mahasiswa Pendidikan Menjadi Calon Guru Profesional - Nurrikza; Nofiana, Putri (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to find out 1) The effect of student perceptions on the interest in the teaching profession to become a teacher. 2) The influence of the family environment on the interest in becoming a teacher. 3) Competencies that must be possessed by professional teachers. It turns out that it is true that student perceptions of the teaching profession have a significant effect on interest in becoming a teacher. This means that students' perceptions of the teaching profession directly have a great influence on the formation of interest in becoming a teacher. In addition, the family environment also has a significant effect on the interest in becoming a teacher. This means that the family environment is indirectly able to have a big influence on students' interest in becoming teachers. Meanwhile, the criteria that must be met by a professional teacher include 4 things, namely: 1) pedagogic competence, namely the teacher's competency in conveying learning material including an understanding of students; 2) personality competence, namely attitude and behavior as a professional teacher figure; 3) social competence, namely the ability to establish relationships with the learning community including teachers, students, and parents of students; and 4) professional teacher competence related to mastery of learning material content.